A Method and an Apparatus for Machining a Tool Steel - Amin, A. K. M. Nurul; Lajis, M. A.; Ismail, Ahmad Faris (2014)
The present invention relates to a method for machining a tool steel workpiece, characterized by the steps of: heating the workpiece surface to a predetermined depth by initiating an induction current using the heat induction coil in real time; simultaneously, contacting the heated workpiece surface with a machining means comprising a coated carbide insert or a polycrystalline cubic boron nitride insert, for machining the workpiece; and wherein the workpiece surface is heated to a minimum temperature of 200-350 °C and the minimum predetermined depth of 2-3 mm. An apparatus for machining the tool steel workpiece is also provided thereof.